Pressurized natural deep eutectic solvents: An alternative approach to agro-soy by-products - Bragagnolo, Felipe Sanchez; Socas-Rodríguez, Bárbara; Mendiola, Jose A.; Cifuentes, Alejandro; Funari, Cristiano Soleo; Ibáñez, Elena (Frontiers in Nutrition, 2022)
Soybeans are among the world's major crops responsible for food and biodiesel production. It is estimated that soybean production left about 651 million metric tons of branches, leaves, pods, and roots on the ground post-harvesting in 2022/23. Besides, such by-products might serve as a significant available and cheap source of high added-value metabolites, such as flavonoids, isoflavonoids, and other phenolic compounds. This work aimed to explore green approaches based on the use of pressurized and gas expanded-liquid extraction combined with Natural Deep Eutectic Solvents (NADES) to achieve phenolic-rich extracts from soy by-products. The total phenolic and flavonoid content of the generated extracts were quantified, and the metabolic profiles of extracts were obtained by UHPLC-ESI-QToF-MS/MS. Pressurized choline chloride:citric acid:water (1:1:11 – molar ratio) at 120 °C resulted in an optimized condition to extract phenolics and flavonoids from agro soy by-products. The extracts obtained from the optimized condition were tested for their potential antioxidant capacity using ROS scavenging capacity. Furthermore, Hansen Solubility Parameters (HSP) were applied to select Natural Hydrophobic Deep Eutectic Solvents (NaHDES) as substituents for n-heptane to defat soybean. Extractions applying NaHDES achieved a similar yield to n-heptane, and their extracts were analyzed by GC-QToF-MS.